Sistem Informasi Penyusunan Rencana Kerja Berbasis Web di Kantor Kesatuan Bangsa dan Politik (kesbangpol) Kota Banda Aceh - Aulia, M Yasir; Idwan, Harry; Hajriyanti, Rahmi (Jurnal Ilmu Komputer dan Teknologi Informasi, 2025)
This study aims to design and implement a Web-based Work Plan Preparation Information System at the National and Political Unity Office (Kesbangpol) of Banda Aceh City. Previously, work plan management was done manually using agenda books, which required more time and effort. With the introduction of the web-based system, data input, reporting, and information storage can be done more efficiently and accessed easily from any location with an internet connection. The research process includes user needs analysis, interface design, database structure planning, and system implementation using specific programming languages. Testing was also conducted to ensure the system functions correctly and meets user expectations. The testing results indicate that this system can improve the efficiency of work plan preparation, speed up reporting processes, and simplify the management of structured data. Furthermore, the system provides easy access to data through devices such as laptops and smartphones, eliminating the need to meet with archive staff. The implementation of this system is expected to enhance productivity, data accuracy, and minimize errors in the work plan management process. It is also hoped that this system can serve as a model for other agencies looking to improve their data management efficiency through digital solutions.